Genome-wide association study revealed genomic regions associated with tuber quality traits in water yam (Dioscorea alata L.) - Fatoumata Ouattara; Paterne A. Agre; Idris I. Adejumobi; Bunmi Olasanmi; Adekemi Stanley; Fatogoma Sorho; Konan E. B. Dibi; Malachy O. Akoroda; Ranjana Bhattacharjee (PLoS ONE, 2026)
Water yam ( Dioscorea alata L.) or greater yam, is an essential species of the Dioscoreceae family in tropical and subtropical regions. The wide geographical distribution is owing to its higher tuber yield, storability, and better nutritional and health benefits compared to many other species. Despite these promising characteristics, water yam remains less preferred by consumers for traditional food products, particularly boiled and pounded yam preparations. Fast and efficient development of superior genotypes that meet farmers and end-users needs have been challenging through classical breeding methods. The objective of the study was to use genome-wide associations to assess the genetics of post-harvest tuber quality, mainly targeting the consumer-preferred traits. A panel of 404 water yam genotypes were assessed to decipher the genomic regions associated with traits such as tuber oxidative browning, dry matter content, and boiled and pounded tuber quality. The Multiple Random Mixed Linear Model was employed for marker-trait association analysis using the naive, Q, and Q + K models, followed by gene annotation and marker or allele substitution effects. Fourteen SNP markers were significantly linked with the assessed tuber quality traits and r 2 values ranged from 0.62 to 10.02%. The gene annotation analysis revealed presence of 32 putative candidate genes playing crucial roles in enzymatic browning and carbohydrate biosynthesis pathways for dry matter accumulation. The molecular information generated in the present study can be deployed for water yam improvement.